The Philippine Star database on the internet an evaluation of precision capability - Ramos, Marielys Ann T.; Faderon, Rosalie B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
The recent years have seen a massive information explosion, and with it a corresponding demand for faster access to more information. Since the introduction of the internet in the 1980s, people preferring to search online have increased exponentially over the last decade. Due to the proliferation of a wide variety of web sites, information has never been more accessible to the users.
In the Philippines, a lot of web sites, electronic archives and online databases area available on the internet. Specifically, a lot of newspapers and publications have made their own web sites to be able to provide the people with online daily news and electronic archives for retrospective searching. Unfortunately, some research studies have uncovered a number of common problems experienced by users regarding searching through information systems. Thus, a contribution of this researcher, this study will make an evaluation of the Philippine Star Database, specifically its capability in producing search results with a higher number of relevant documents and irrelevant documents, and in filtering out unwanted documents. This is called measuring the precision ratio or precision capability of the information retrieval system.
The descriptive method of research was used for this study. To determine the population, the researcher made use of the random sampling method. One hundred users/searchers with real information needs were randomly selected from the customers of the Netoholic anonymous. Basically the researcher compared the precision ratios of the non-delegated searches of the 100 randomly selected users/searchers to the precision ratios of the delegated searches done by an intermediary. In this study, the researcher served as the intermediary.
After the execution of the evaluation program, results have shown that the intermediary played a significant role in more successful searches for the users/searchers, provided that the major factors contributing to high precision results have been met. Based on the findings, the researcher concluded that the precision capability of the Philippine STar Database ranges from average to highly precise provided that the following factors have been met: 1. the search terms or topics of information that the user/searcher needs should be within the coverage of the database. The Philippine Star Database contains information based on the contents of its web site, The Philippine Star. Since it is an online newspaper, naturally the coverage of the database is limited to topics which are of news item material, or topics which are usually published in newspapers. 2. Users/searchers should at least be familiar with the database. Results have shown the familiarity regarding the use of the database contributed to having high precision results. The database has its own search strategies different from other common database. Familiarity with the database, search strategies it requires that the topics of coverage will guarantee the user/searchers with satisfying, if not high, precision results. 3. Familiarity with the internet environment. Users who have been exposed to the internet for a long time do know how to get their way around in cyberspace. Unfamiliarity with the Philippine Star Database was compensated with familiarity with web sites and other information systems.
The researcher recommends that the Philippine Star broaden topics of coverage so that the database can still be used for research, even for topics of scientific and general reference nature. It is also recommended that large fonts be used to indicate that there are search strategies available to make more successful searches and place its navigational links where these are highly visible to the users. Lastly, it is recommended that the Netoholic anonymous hire an information specialist to supervise some of its customers, and to add some personal touch to its quality of service.
Undergraduate thesis(B.L.I.S.)--University of the Philippines, Diliman
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Online databases -- Evaluation. -- Philippines; Philippine Star Database; Web sites -- Evaluation. -- Philippines; Database searching -- Philippines